Transcription Factor ELF1 Activates MEIS1 Transcription and Then Regulates the GFI1/FBW7 Axis to Promote the Development of Glioma - Meixiong Cheng; Yi Zeng; Tian Zhang; Min Xu; Zhili Li; Yaqiu Wu (Elsevier, 2021)
Glioma is the most common malignancy in the central nervous system with no immediate prospect of a cure. Comprehensive understanding on the pathogenesis of the disorder contributes to a better outcome. Herein, we aimed to investigate whether transcription factors erythroblast transformation-specific (ETS) transcription factor (ELF1), myeloid ecotropic viral integration site 1 (MEIS1), and growth factor independence 1 (GFI1)/F-box/WD repeat-containing protein 7 (FBW7) mediate progression of glioma. ELF1, MEIS1, and GFI1 were upregulated in glioma cells and tissues, as ELF1 was correlated with poor prognosis. Bioinformatics analysis identified the binding between ELF1 and MEIS1 as well as between GFI1 and FBW7, confirmed by chromatin immunoprecipitation (ChIP) experiments. Functional experiment indicated that silencing of ELT1 decreased MEIS1 expression and that overexpression of MEIS1 increased GFI1 expression by activating GFI1 enhancer but decreased FBW7 expression. Importantly, silencing of ELF1 decreased the capacities of proliferation, migration, and invasion of glioma cells whereas it increased apoptosis, supported by increased capase-3 and decreased matrix metalloproteinase-9 (MMP-9) and proliferating cell nuclear antigen (PCNA) expression. Moreover, an in vivo experiment confirmed the inhibitory role of silenced ELF1 in tumor growth, with a decreased level of MEIS1 and GFI1. Taken together, our study elucidated a potential mechanism that ELF1 promoted cell progression by increasing GFI1 and METS1 as well as decreasing FBW7 expression in glioma.